QUANTITATIVE METHOD ANALYSIS LEVEL OF COMMUNITY PARTICIPATION IN HUMAN RESOURCE DEVELOPMENT - Reinald stevianes. L; Muammar Khadafi; Iswarijaya; Syarif Ahmad; Wan Iwan Darmawan; Nurhandika Sepvia Putri; Uci Liharyanti; Santi Sihombing; Novita Nasution; Ongky Parmadhie Putra (Universitas Efarina, 2023)
This research aims to determine the level of community participation in Tanjungpiang regarding Human Resources development. The sampling technique used simple random sampling with a sample of 75 people. Data collection techniques use observation, interviews, literature study and questionnaires. The research results show that; 1) the level of community participation is 56.8%, which is in the poor/less influential category, 2) Human Resources development is 58.5%, which is in the poor/less influential category, 3) the level of community participation in Human Resources development.